Kepatuhan Pembayaran Pajak Kendaraan Bermotor pada Unit Pelaksanaan Teknis (UPT) Samsat Rumbai - Novita Yuriska Br Sitorus; Della Anggely Br Damanik; Elly Nielwaty (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
In Indonesia, many people own motorized vehicles but the tax distribution is still low. This shows that people are not obedient in making taxpayer payments. This research was conducted to find out and analyze how the compliance of taxpayers in Rumbai Subdistrict in increasing motor vehicle tax revenue. The research method used is a descriptive qualitative approach. However, there are still challenges in terms of socialization and public awareness of motor vehicle tax payments. Therefore, further efforts are needed in improving technological infrastructure and educational campaigns so that taxpayers can be more optimal in supporting effective and efficient public services. Because the higher the level of taxpayer compliance, the higher the local revenue will be obtained.